On the Historical Development of Confucianists’ Moral Ideas and Moral Education - Yang, Shaogang (ETHICS IN PROGRESS, 2013)
The Confucian ethics which is the main body of the Chinese traditional culture has established its “basic morality” or “mother morality” not only in China, but also in some of the Asian countries. It is formed in the long historical development of more than 2000 years. First of all, it had the contention of a hundred schools of thought in the Pre-Qin Dynasty, and the Confucianist thought with its own colors was formed at that time. When Dong Zhongshu made his suggestions that restrained all other schools but only respected Confucianism, the predominance of Confucianism over the political life had been defined in Chinese society. After the later generations’ cooperating thing of diverse nature with unity of opposites, it was developed into the idealist philosophy of the Song (960 -1279) and Ming (1368-1644). Dynasties, which combined Confucianism, Buddhism and Daoism. The critical development of the modern Chinese society to Confucianist thought made us scholars have a timely reflection on the Confucian ethics. The requirement of constructing a harmonious world in the present time made us further considerate the moral education with Confucianist ethics.